Brief Report: Patterns and Secular Trends in Use of Immunomodulatory Agents During Pregnancy in Women With Rheumatic Conditions. Issue 5 (27th April 2016) - Desai, Rishi J.; Huybrechts, Krista F.; Bateman, Brian T.; Hernandez‐Diaz, Sonia; Mogun, Helen; Gopalakrishnan, Chandrasekar; Patorno, Elisabetta; Kim, Seoyoung C.
Abstract : Objective: To describe patterns and secular trends in the use of immunomodulatory agents in pregnant women with systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), psoriatic arthritis (PsA), or ankylosing spondylitis (AS). Methods: We identified a cohort of women with SLE, RA, PsA, or AS enrolled in public (Medicaid, 2001–2010) or private (Optum Clinformatics, 2004–2012) health insurance, and we included women filling prescriptions for immunomodulatory agents (including steroids, nonbiologic disease‐modifying agents, and biologic agents) in the 3‐month period immediately prior to their pregnancies. The proportion of women continuing or discontinuing individual agents during pregnancy was reported. Annual prescription fill rates, estimated after accounting for patient characteristics and random variability from year to year in mixed‐effects regression models, were used to conduct time trends analysis. Results: We included 2, 645 women being treated with immunomodulatory agents prior to pregnancy. More women with PsA or AS stopped filling prescriptions for immunomodulatory agents during pregnancy (61%) than women with SLE (26%) or women with RA (34.5%). From the first to the third trimester, the proportions of women filling prescriptions for immunomodulatory agents decreased across all indications. Overall, steroids and hydroxychloroquine were the most frequently used agents in pregnancy (48.4% and 27.1%, respectively). The rates (reported per 100 deliveries in our cohort) for steroid prescription fills during pregnancy decreased significantly from 54.4 in 2001 to 42.4 in 2012, while rates for biologic agents increased from 5.1 in 2001 to 16.6 in 2012 ( P < 0.001 for both trends). Conclusion: Steroids and hydroxychloroquine remain the most widely prescribed treatment options in pregnancy, but the use of biologic agents is becoming increasingly common.